Determinants of Financial Reporting Timeliness: An Empirical Study in Indonesian Banking Firms (2020–2022) - Istanti, Sri Layla Wahyu; Ningrum, Agustina Khristina (Economics and Business Solutions Journal, 2025)
This study investigates the determinants of financial reporting timeliness in Indonesian banking firms. Specifically, it examines the effects of firm age, firm size, and financial distress on the punctuality of financial reporting among banks listed on the Indonesia Stock Exchange (IDX) during 2020–2022. Using a quantitative associative approach, purposive sampling was employed to select 27 banking firms that consistently published audited annual reports during the observation period, resulting in 81 firm-year observations. Logistic regression analysis, performed with SPSS version 25, was used to test the hypotheses. The findings reveal that firm age has a positive but insignificant effect, firm size has a negative and significant effect, and financial distress has a negative but insignificant effect on the timeliness of financial reporting. The adjusted R² of 0.282 suggests that the independent variables explain 28.2% of the variance, with the remainder influenced by factors outside the model. This study contributes to the literature by highlighting the unique dynamics of financial reporting timeliness in the Indonesian banking sector, particularly during a period characterized by heightened regulatory scrutiny. The results imply that larger firms face greater complexity in timely reporting, whereas financial distress exerts limited influence. This research offers insights for regulators, investors, and corporate managers in understanding the structural and operational challenges that affect reporting timeliness.
Keywords: Financial distress; Firm age; Firm size; Timeliness of financial reporting